2016
DOI: 10.3389/fpsyg.2016.01575
|View full text |Cite
|
Sign up to set email alerts
|

Entraining IDyOT: Timing in the Information Dynamics of Thinking

Abstract: We present a novel hypothetical account of entrainment in music and language, in context of the Information Dynamics of Thinking model, IDyOT. The extended model affords an alternative view of entrainment, and its companion term, pulse, from earlier accounts. The model is based on hierarchical, statistical prediction, modeling expectations of both what an event will be and when it will happen. As such, it constitutes a kind of predictive coding, with a particular novel hypothetical implementation. Here, we foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 121 publications
(142 reference statements)
2
26
0
Order By: Relevance
“…The present Deep Improviser, while yet shallow, when comprised of CNN and RNN probably imitates some of the sequential aspects of time series models. But we also plan in the longer run to integrate Deep Improviser with algorithmic approaches based on information theoretic and perceptual decision-making models [46,47].…”
Section: Discussion Conclusion and Future Workmentioning
confidence: 99%
“…The present Deep Improviser, while yet shallow, when comprised of CNN and RNN probably imitates some of the sequential aspects of time series models. But we also plan in the longer run to integrate Deep Improviser with algorithmic approaches based on information theoretic and perceptual decision-making models [46,47].…”
Section: Discussion Conclusion and Future Workmentioning
confidence: 99%
“…Examples of these are Nengo (Eliasmith, 2013), neural blackboard architectures (Van der Velde and De Kamps, 2006), and the previously mentioned Smolensky and Legendre (2006). Further, the use of conceptual spaces in cognitive architectures is an area of active research, as seen in, for example, Forth et al (2016); Lieto et al (2017). Whilst the current work does not model key aspects of human cognition such as dynamics or action selection, it provides a model of compositionality that can be utilized by these architectures in representing inputs and how they may combine to form novel representations.…”
Section: Related Workmentioning
confidence: 99%
“…Bearing in mind eye movement research in response to auditory experiment has shown results in pupil dilation response [45], the present ndings on motor modulation of attentional processing would we extended by a broader motor response. Moreover, the model would modify the Information Dynamics of Thinking (IDyOT) model for language and music of Forth and colleagues [44] may bear in mind previous motor response and unexpected external stimulus. Forth and colleagues proposed a mechanism for predicting when a perceptual event will happen, given an existing sequence of past events, which may be musical or linguistic [44].…”
Section: Conclusion: Improve Of Modeling Novel Response Due To Pmentioning
confidence: 99%
“…Moreover, the model would modify the Information Dynamics of Thinking (IDyOT) model for language and music of Forth and colleagues [44] may bear in mind previous motor response and unexpected external stimulus. Forth and colleagues proposed a mechanism for predicting when a perceptual event will happen, given an existing sequence of past events, which may be musical or linguistic [44].…”
Section: Conclusion: Improve Of Modeling Novel Response Due To Pmentioning
confidence: 99%